A novel option for prandial insulin therapy: inhaled insulin. Issue 8 (16th November 2016) - Dailey, George; Ahmad, Aakif; Polsky, Sarit; Shah, Viral
ABSTRACT: Many adults with type 2 diabetes (T2D) do not achieve or maintain glycemic targets on oral antidiabetes drugs (OADs) alone and require insulin therapy. Although initiating basal insulin is common when treatment needs to be intensified, individualization of therapy (in line with current guidelines) may lead more health care professionals (HCPs) to add rapid-acting insulin (RAI) to OAD regimens for treatment of postprandial hyperglycemia to achieve glycated hemoglobin (A1C) targets. HCPs and patients are concerned about the burden associated with injections. Inhaled Technosphere® insulin (inhaled TI) – as an alternative to injectable bolus doses of prandial insulin – may increase patient and HCP willingness to intensify therapy and improve compliance with more complex regimens. Clinical studies have shown that inhaled TI is effective and well tolerated as a prandial insulin, and has the potential to improve treatment satisfaction and quality of life in adults with T2D. The favorable pharmacokinetic profile of inhaled TI (i.e., a very rapid onset of action and a short duration of anti-hyperglycemic effect) may reduce the risk of insulin stacking (overlapping effects of RAI injections taken < 4 hours apart) and postprandial hypoglycemia. In this review, we present inhaled TI as an alternative to OADs or injected insulin as adjunctive therapy, for consideration by HCPs striving to achieve glycemic targets for their patients.